Pengaruh Analisis Fundamental Terhadap Harga Saham Perbankan Di Bursa Efek Indonesia Tahun 2015-2019 - Atti Rasnawati (CITRA EKONOMI, 2021)
This study raises the issue of fundamental analysis of stock prices with fundamental factors, namely CAR, NPL, NIM, LDR and GCG in banking companies listed on the Indonesian stock exchange. The purpose of this study is to examine and determine the effect of fundamental factors on stock prices. The results of this study, CAR has a positive and insignificant effect on stock prices, LDR has a negative and insignificant effect on stock prices, NPL and NIM, has a negative and significant effect on stock prices, GCG has a significant effect on stock prices. The F test results, namely CAR, NPL, NIM, LDR and GCG jointly affect stock prices. The R2 value of stock price variations can be explained by the CAR, NPL, NIM, LDR and GCG variables.